ECOLOGICAL LEARNING MATERIAL: (THE DIET OF RICE-FIELD RATS (Rattus argentiventer Rob. & KIoss) TOWARD UNSYNCHRONIZED PLANTING SYSTEM OF PADDY FIELD) - PUGUH KARYANTO (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2005)
This is the research about the diet of rice-field rats lived in unsynchronized planting system of paddy field, a condition when paddy field are heterogenous in term of stages. At that kind of field, carbohydrate supplies, in a form of booting to harvesting of paddy are available at all the time. That condition gives benefit to the rats, since those stages supply the most preference diet and also supply a lot food that act as the main factor support its reproduction . The preference of that best supportingfood for reproduction were proved by the presence of it and the prevalence of reproduction respectively. The results of this research can be use as an ecological learning material for he who wants to study about eco-physiology.This research was carried out at all stages of rice plant toward unsynchronized planting system of paddy field of Sukoharjo. Some systematic steps of this research were catching the rat by using the linear trap barrier system (LTBS)and by using the fumigation, determine its reproductive state which was according to Allen (1920), identify the diet by ventriculus analysis and then give analyze to the data .Ventriculus analysis showed that rice-field rat prefers to consume the energy-rich food in a form of booting to harvesting paddy stages in every stage of rice. That pattern of food consumption will trigger its reproduction respectively, thus, the reproduction occur continuously. At that case, carbohydrate can be guess as proximate and ultimate limiting factors that lead the reproduction to occur. That eco-physiology phenomenon showed the effect of environment toward the physiology and behavior of organism. That's the ecological material to learn.